2014
DOI: 10.1002/jaba.174
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of video modeling with embedded instructions to teach implementation of stimulus preference assessments

Abstract: A multiple baseline design across participants was used to evaluate the effects of video modeling with embedded instructions on training teachers to implement 3 preference assessments. Each assessment was conducted with a confederate learner or a child with autism during generalization probes. All teachers met the predetermined mastery criterion, and 2 of the 3 demonstrated skill maintenance at 1-month follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 16 publications
3
47
1
Order By: Relevance
“…Though such standardizations have already been explored in foster care settings (Whitehouse et al 2014), the full potential of this modality has yet to be realized. Ultimately, standardization of stimuli may reduce the need for specialty training necessary for the implementation of preference assessments (see Pence et al 2012 andRosales et al 2015) and improve opportunities for children with autism and other developmental disabilities to make choices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though such standardizations have already been explored in foster care settings (Whitehouse et al 2014), the full potential of this modality has yet to be realized. Ultimately, standardization of stimuli may reduce the need for specialty training necessary for the implementation of preference assessments (see Pence et al 2012 andRosales et al 2015) and improve opportunities for children with autism and other developmental disabilities to make choices.…”
Section: Discussionmentioning
confidence: 99%
“…An electronic pictorial format may also allow for standardization of presentation of stimuli and reduced response effort of implementation (see Whitehouse et al 2014). Research has shown that preference assessment implementation requires specialized instruction (Pence et al 2012;Rosales et al 2015). Therefore, refinements to preference assessment modality that may eventually lead to standardization of stimulus presentation and reduce associated effort with training and implementation should be explored.…”
Section: Introductionmentioning
confidence: 98%
“…In a search of the extant literature, we identified ten studies that trained staff to implement SPAs (Bishop and Kenzer 2012); Graff and Karsten (2012b); (Lavie and Sturmey 2002;Lerman et al 2008;Lerman et al 2004;Pence et al 2012;Rosales et al 2015;Roscoe and Fisher 2008;Roscoe et al 2006;Weldy et al 2014). No previous study trained staff to implement all four components previously discussed.…”
mentioning
confidence: 96%
“…No previous study trained staff to implement all four components previously discussed. When considering each of the components individually, in no study were staff trained how to choose the most appropriate type of SPA to conduct with consumers, one study reported training staff how to identify stimuli to use during SPAs based on best practice (Bishop and Kenzer 2012), all ten studies trained staff to conduct one or more SPAs, and six studies trained staff to score and interpret data obtained from SPAs (Bishop and Kenzer 2012;Graff and Karsten 2012b;Rosales et al 2015;Roscoe and Fisher 2008;Roscoe et al 2006;Weldy et al 2014). More studies are needed to identify training approaches that lead to staff implementing all of the components necessary to independently administer SPAs.…”
mentioning
confidence: 99%
See 1 more Smart Citation